Using the zebrafish lateral line to uncover novel mechanisms of action and prevention in drug-induced hair cell death - Stawicki, Tamara M.; Esterberg, Robert; Hailey, Dale W.; Raible, David W.; Rubel, Edwin W (Frontiers in Cellular Neuroscience, 2015)
The majority of hearing loss and balance disorders are caused by the permanent loss of mechanosensory hair cells of the inner ear. Identification of genes and compounds that modulate susceptibility to hair cell death is frequently confounded by the difficulties of assaying for such complex phenomena in mammalian models. The zebrafish has emerged as a powerful animal model for genetic and chemical screening in many contexts. Several characteristics of the zebrafish, such as its small size and external location of mechanosensory hair cells within the lateral line sensory organ, uniquely position it as an ideal model organism for the study of hair cell toxicity. We have used this model to screen for genes and compounds that affect hair cell survival during ototoxin exposure and have identified agents that would not be expected to play a role in this process based on a priori knowledge of their function. The identification of such agents yields better understanding of hair cell death and holds promise to stem hearing loss and balance disorders in the human population.